PENGEMBANGAN MEDIA BOOKLET UNTUK MENINGKATKAN PENGETAHUAN TENTANG KESIAPAN MENJADI ORANG TUA - Ernawati, Ernawati; Megawati, Hermeilia; Tsalisa M, Asma; Alyani, Nazhifa; Salsabila, Fressika (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2023)
This research aims to develop a booklet as a medium to introduce knowledge about parental readiness. The method used in this research is Research and Development (R&D). The development model in this research is the ADDIE development model, which consists of 5 steps: Analysis, Design, Development, Implementation, and Evaluation. The research respondents consist of 13 married individuals in Pasirtanjung Village, Tanjung Sari District, Bogor Regency, West Java, who do not yet have children. Questionnaires were also given to content experts and media experts. The results of this research show that, according to the 13 respondents, the booklet received a score of 3.1748, which falls into the 'Good' category. The assessment by content experts received a score of 3.9091, which also falls into the 'Good' category, and the assessment by media experts received a score of 4, falling into the 'Very Good' category. The results of the t test also show a significance value smaller than 0.005. These results show that there is an increase in knowledge about parenting readiness after the booklet was given. The recommendations from this research indicate that the booklet can be used to increase knowledge about preparedness for parenthood.